Óleos essencias de Nectandra grandiflora e Ocotea acutifolia: rendimento, composição química e atividades biológicas - Silva, Daniela Thomas da (2013)
This work aimed to contribute with the knowledge and generation of new and useful products to humans and animals from native species, namely, Nectandra grandiflora Nees and Ocotea acutifolia (Nees) Mez. Essential oils (EO) of these species were extracted by hydrodistillation with Clevenger apparatus in order to determine the yield (% w/w) and chemical composition using gas chromatography coupled to mass spectrometry (GC-MS). Analyzes concerning the effect of seasonal variability on the yield and composition of EO obtained from leaves of N. grandiflora for a year were also performed in order to verify the best time for collecting the plant material. Additionally, the evaluation of the sedative/anesthetic properties of EO of leaves of O. acutifolia in silver catfish, and the larvicidal potential of EO of leaves of N. grandiflora against Odonata larvae were performed. Chemical analysis of EO of leaves, inflorescence and bark of N. grandiflora showed that they are composed mainly of sesquiterpenoids, being dehydrofukinone the major compound. For EO of leaves and inflorescences of O. acutifolia, we identified the sesquiterpenoid caryophyllene oxide as major compound. The leaves of EO of N. grandiflora showed significantly higher yield in the spring (0.75%), which coincides with the flowering period of the species, whereas the lowest yield was obtained during the winter (0.39%).However, the chemical composition was not influenced by the seasons of collection. There were only small quantitative differences in the proportion of the major sesquiterpenoids in the EO of the leaves of N. grandiflora. The compound dehydrofukinone predominated during all the period, and was found at higher concentrations in the winter. In the spring, there was an increase of the contents of bicyclogermacrene, and a decrease of the concentrations of dehydrofukinone. The leaves of EO of O. acutifolia showed anesthetic activity against juvenile silver catfish (Rhamdia quelen) at concentrations ranging from 300-900 μL L-1. The concentration of 100 μL L-1of N. grandiflora EO was not effective to the control of larvae of the Odonata order.